Survivorship Bias in Performance Studies - Brown, Stephen J.; Goetzmann, William; Ibbotson, Roger G.; Ross, Stephen A. (Review of Financial Studies, 1992)
Recent evidence suggests that past mutual fund performance predicts future performance. We analyze the relationship between volatility and returns in a sample that is truncated by survivorship and show that this relationship gives rise to the appearance of predictability. We present some numerical examples to show that this effect can be strong enough to account for the strength of evidence favoring return predictability. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.